An upgrade of the materials irradiation facility with in-situ electrical resistivity measurement at the Demokritos TANDEM accelerator - Theodorou, A.; Kotsina, Z.; Axiotis, M.; Apostolopoulos, G. (HNPS Advances in Nuclear Physics, 2019)
As an important part of fusion materials research, evaluation of radiation damage in fusion materials has been emphasized more than a half century. In order to improve our understanding of radiation damage in fusion materials, an upgrade has been performed of the materials irradiation facility IR2, which is located at the NCSR “Demokritos” 5.5 MV TANDEM accelerator. The upgraded facility allows irradiation at higher ion beam currents while ensuring that the target temperature remains below 10 K. It provides in-situ electrical resistivity measurements on several samples for real-time monitoring of radiation damage as well as in-situ post-irradiation annealing up to 300 K. The upgraded IR2 facility has been successfully employed in radiation damage and recovery studies of metallic materials with applications in fusion research.